611 Mild cognitive impairment is associated with subclinical left ventricular dysfunction as assessed by global longitudinal strain in hypertensive patients. (8th December 2021) - Ferruzzi, Germano Junior; Visco, Valeria; Loria, Francesco; Galasso, Gennaro; Iaccarino, Guido; Vecchione, Carmine; Ciccarelli, Michele
Abstract: Aims: Left ventricular global longitudinal strain (GLS) detects subtle systolic abnormalities in various cardiovascular conditions, which represent significant risk factors for cognitive impairment and stroke. Specifically, GLS has emerged as a more precise myocardial function measure than left ventricular ejection fraction (LVEF). This study investigated the relationship of GLS with mild cognitive impairment (MCI) in hypertensive patients. Methods and results: From February 2020 to October 2021 were enrolled hypertensive patients without atrial fibrillation and/or cerebrovascular and/or neurodegenerative diseases. Complete demographic, clinical characteristics, laboratory analyses, conventional echocardiographic parameters were collected. Finally, MCI was defined by accurate the Quick Mild Cognitive Impairment (QMCI) Screen corrected for age and education. This score explores spatial and temporal orientation, registration, delayed recall, clock design, logical memory, and verbal fluency in a brief time (5 min—score 0–100); a compliance questionnaire (Morisky medication adherence scale); a questionnaire on nutritional status (MNA). 81 hypertensive patients [66 ± 7.27 years; 9 (11%) female] were included in the study. Concerning echocardiographic evaluation, LVEF was 50.47 ± 9.95% and mean GLS was −16.00 ± 3.66. Mean QMCI corrected for age and education was 56.45 ± 9.37, and MCI was detected in 21 patients (26%). When comparing the patients with MCI (QMCItot <49.4) and without MCI (QMCItot >49.4), a statistically significant difference of GLS values was detected (no MCI: −16.52 ± 3.66 vs. MCI: −14.18 ± 3.23; P = 0.032); on the other hand, the two groups did not differ in LVEF (no MCI: 50.58 ± 9.70 vs. MCI: 48.86 ± 11.93; P = 0.864). Furthermore, excluding patients with FE ≥ 45% from the analysis, a statistically significant linear regression was observed between QMCI (corrected for age and education) and the GLS ( P = 0.014) (Figure 1 ). Conclusions: Compromised GLS, but not LV EF, is related to MCI in hypertensive patients who are free of clinical dementia, stroke, and neurodegenerative disease. Moreover, our study demonstrates for the first time the existence of a significant association between the QMCI and GLS; consequently, GLS could be an additional parameter in clinical practice for early recognition of MCI. However, studies on a larger population will be needed to confirm this association.